Is bigger better? Driving factors of POTW performance in New York. (15th May 2018) - Rahm, Brian G.; Morse, Natalie; Bowen, Michelle; Choi, Jun; Mehta, Dhaval; Vedachalam, Sridhar
Abstract: Like many regions around the world, New York State, USA, faces challenges in meeting wastewater treatment quality standards because of aging infrastructure, limited funding, shifting demographics and increasingly stringent environmental regulations. In recent decades construction of new wastewater treatment and distribution infrastructure in NY has most often occurred in exurban communities and suburban developments that are less dense than traditional urban cores. Here, we examine the role of size and capacity utilization on wastewater treatment effectiveness with respect to critical effluent parameters, and additionally explore which common facility engineering controls influence water quality treatment using a unique dataset of descriptive information. Our results challenge conventional wisdom, suggesting that the largest facilities (>30, 000 m 3 /d), not the smallest (<300 m 3 /d), discharge TSS, BOD, and coliform at significantly higher relative effluent concentrations (i.e., the ratio of discharged concentrations to allowable limits). Capacity utilization was also positively correlated to higher concentrations of TSS, BOD, and coliform effluent concentrations in larger facilities, though those concentrations were often within regulated limits. This implies that smaller-sized facilities may perform better in terms of environmental quality, but that the largest facilities demonstrate efficiency in the sense that they are not "over-treating" wastewater while avoiding violations. Results from NY suggest that medium sized facilities (300–30, 000 m 3 /d) are sophisticated enough to incorporate appropriate unit processes, and employ operators with sufficient training and oversight, to reach treatment outcomes that are both reliable and of high quality. Highlights: In NY, small POTWs often achieve lower effluent contaminant concentrations. Medium-sized POTWs routinely perform the best in terms of water quality. Drivers of performance for small facilities are different than for larger facilities. The largest facilities maintain effluent concentrations closer to regulated limits.